GURU DAN MURID DALAM PERSEKTIF AL QUR’ANDAN HADITS - Iskandar Yusuf; Iskandar (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2021)
Teachers in the perspective of Islamic education are people who are responsible for the development of all potential students. If we look functionally the word teacher can be interpreted as a giver or distributor of knowledge, skills. A teacher has a sense of responsibility towards his duties as a teacher. As said by Imam Ghazali that "the task of educators is to perfect, clean, perfect and bring the human heart to Taqarrub to Allah SWT. While students are creatures who are in the process of development and growth according to their respective natures, where they really need consistent guidance and direction towards the optimal point of their natural abilities. Based on this understanding, students can be characterized as people who are in need of knowledge or knowledge, guidance and direction.